The Role of Rumah Baca Soka as a Community Reading Center in Building a Culture of Literacy - Luthfi Eri Ardana; Sungkowo Edy Mulyono (Yayasan Keluarga Guru Mandiri, 2025)
Community Reading Centers (CRC) hold a critical role in educating the public and expanding access to knowledge, functioning as literacy centers, agents of social change, character builders, and skill developers. This study aims to determine the role of Rumah Baca Soka as a community reading center in building a culture of literacy within its community. Utilizing a qualitative method with a case study design, data were collected through direct observation, in-depth interviews, and documentation, and subsequently analyzed using the Miles and Huberman interactive model. The findings reveal that Rumah Baca Soka, as a community reading center, plays a strategic role in building community literacy through various functions: serving as an information center, broadening horizons and knowledge, providing educational entertainment, facilitating character development, and offering skills training. Strong community enthusiasm, volunteer involvement, an adequate book collection, and external support support the success of this CRC. Scientifically, this research contributes to enriching the literature on CRCs as community-based empowerment spaces that serve dual functions: as literacy centers, social interaction spaces, and means of developing life skills.